The Relationship Between Peak Take-off Force, Maximum Center of Mass Height, and Successful Block Performance in Volleyball Middle Blockers - Qadoori, Rafid Habib; Ahmed Walid Abdulrahman; Safaa A. Ismaeel (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The research problem revolved around the blocking skill in volleyball from position number (3), performed by the player known as the (Middle Blocker). The core issue is this player's inability to stop the attack of the opposing team's (Middle Hitter) to score a direct point or to sufficiently reduce the ball's speed. Often, the ball deflects off parts of the blocker's fingers and goes out of bounds, leading directly to a lost point. Additionally, most points scored by the opposing team resulted from executing the quick spike attack from position (3) by their (Middle Hitter). The study aimed to: (1) Extract the peak instantaneous force generated by the legs from three different stances at the moment of take-off during block execution. (2) Extract the maximum vertical height of the body's center of mass during the flight phase. (3) Find the correlation between these biomechanical variables and the accuracy of the block in youth volleyball players. Three types of tests were conducted on the study sample, which consisted of two specialized (Middle Blocker) players.